Modelling Of Toddlers Stunting Prevention in The First Thousand Days of Urban Area Life - sugeng suhardi wiyono; Syarif Darmawan; Mega Damayanti; Amsiah Amsiah; Miranti Miranti (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2022)
Indonesia faces the problem of stunting by 30.8 %. Judging from the severity, children aged 3 years with severe stunting in boys have 15.0 points lower in reading ability and in they have lower 11.0 points compared to mild stunting, which affects a decrease in intelligence (IQ), therefor they learning achievement becomes low. The purpose of the study was to obtain a model for preventing stunting under five during the first thousand days of life. This is an analytic observational study with a case-control design. The case sampling was all stunted toddlers and controls were tall normal children who were matched for age and sex each as many as 28 children. Height was measured using a microtoise, nutrient intake was measured by the food recall using method 24 hours ago, characteristics data were measured by using interview and observation method. The inclusion criteria were children aged 6-59 years while the exclusion criteria in this study were toddlers with physical disabilities. Bivariate analysis showed that the variables that were significantly related to stunting (p<0,05) were the length of the baby born 47,0 cm (p=0.005) OR 4,958 (95% CI: 1,529 -15,987), the mother's height 150,0 cm (p =0,01) OR 4,128 (95%CI: 1,277 – 13,348), father's education (≤Junior High School) p=0,006; OR 5,169 (95% CI: 1,520 – 17,580, and family income (p=0,012) Rp 2,000,000; OR 9,800 (95%CI: 1,116 – 86,041) Multivariate analysis for stunting prevention modelling, namely mother's height <150,0 cm has a risk of 8,578 times to born stunted babies after controlling for the length of the baby, energy intake, protein intake, colds, exclusive breastfeeding, additional food for pregnant women, washing hands with soap and early initiation of breastfeeding.